2007
DOI: 10.1136/emj.2007.046250
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral line dead space: an unrecognised phenomenon?

Abstract: Objective: To determine if peripheral intravenous cannula dead space is taken into account when setting up intravenous infusions (in particular nitrate infusions) in the emergency department. Method: A postal survey of UK emergency departments. Results: Of the 143 (58%) of UK departments who responded, only 15% reported priming the cannula before commencing the nitrate infusion. Conclusions: Knowledge of peripheral intravenous cannula dead space in UK emergency departments is very poor and, as a result, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The deadspace of intravenous cannulae ranges from 0.1 ml to 0.3 ml, depending on the manufacturer and the size of the cannula . The deadspace of tunnelled lines is much greater: a 7‐Fr Hickman ® line has a deadpsace of 0.8 ml and a 6‐Fr Portacath ® a deadspace of 1.2 ml, equating to 40–60 mg suxamethonium (50 mg.ml −1 ) or 8–12 mg atracurium (10 mg.ml −1 ) . In our hospital, 10‐cm extensions are often added to intravenous cannulae, particularly when a cannula without an injection port has been used, which increases the measured deadspace by > 1.5 ml.…”
mentioning
confidence: 84%
“…The deadspace of intravenous cannulae ranges from 0.1 ml to 0.3 ml, depending on the manufacturer and the size of the cannula . The deadspace of tunnelled lines is much greater: a 7‐Fr Hickman ® line has a deadpsace of 0.8 ml and a 6‐Fr Portacath ® a deadspace of 1.2 ml, equating to 40–60 mg suxamethonium (50 mg.ml −1 ) or 8–12 mg atracurium (10 mg.ml −1 ) . In our hospital, 10‐cm extensions are often added to intravenous cannulae, particularly when a cannula without an injection port has been used, which increases the measured deadspace by > 1.5 ml.…”
mentioning
confidence: 84%
“…26 Central catheters may contain up to 0.5 mL of dead space, which may be problematic for medications with low-volume infusion rates. 26 This issue may apply to medications given via non-free-flowing or longer catheters.…”
Section: Administration Techniquesmentioning
confidence: 99%
“…26 Central catheters may contain up to 0.5 mL of dead space, which may be problematic for medications with low-volume infusion rates. 26 This issue may apply to medications given via non-free-flowing or longer catheters. In addition to fully priming infusion catheters before administration of the infusion is started, common infusions given during codes should be given into free-flowing catheters or directly into the most proximal port to allow for quick delivery.…”
Section: Administration Techniquesmentioning
confidence: 99%
“…Several studies have shown that both the dead space volume of the intravenous catheter and the carrier rate are important with regards to achieving a steady state. [80][81][82][83] The optimal setup would infuse insulin via the peripheral venous catheter or central venous catheter lumen with the smallest dead space volume, while at the same time fixing the carrier solution rate at a minimum of 20 ml/h. In order to minimize the effect of dead space, the insulin infusion line should be connected to the carrier solution line in a position as close to the intravenous catheter as is physically possible.…”
Section: Logistic Concernsmentioning
confidence: 99%